Development of A Smart Monitoring System for IoT – Based Tide Observation - Indah Purnama Sari; Asrar Aspia Manurung (Al'adzkiya International of Computer Science and Information Technology (AIoCSIT) Journal, 2025)
This research presents the development of a smart monitoring system for real-time tide observation using Internet of Things (IoT) technology. The system is designed to monitor sea level fluctuations continuously and transmit data wirelessly to a cloud-based platform for remote access and analysis. The hardware consists of ultrasonic sensors for water level measurement, a microcontroller for data processing, and wireless communication modules for data transmission. The collected data can be accessed through a web-based dashboard or mobile application, enabling users to monitor tidal patterns from anywhere at any time. The system also incorporates alert notifications when water levels reach predetermined thresholds, providing early warning capabilities for coastal communities. Testing results demonstrate that the system can accurately measure tidal changes with minimal error and successfully transmit data in real-time. This IoT-based tide monitoring system offers a cost-effective and efficient solution for oceanographic observation, coastal management, and disaster mitigation applications. The implementation of this technology contributes to improved maritime safety, fishing activities planning, and environmental monitoring in coastal areas.